Os Sino-moçambicanos da Beira. Mestiçagens Várias - Eduardo Medeiros (Cadernos de Estudos Africanos, 2007)
The focus of this article is on cross-cultural encounters, involving African, European and Asian identities, that occurred in colonial Mozambique in the 19th and 20th. It suggests that the colonial ideology of «cultural separatism» and the manipulative management of socio-cultural differences between African, Chinese, Indian and Portuguese populations did not succeed in supplanting the spontaneous processes of hybridization and transculturation of these communities. It generated continuously new identities and, with them, also new tensions and social recompositions.